2014
DOI: 10.1126/scisignal.2005329
|View full text |Cite
|
Sign up to set email alerts
|

Invasive breast carcinoma cells from patients exhibit Mena INV - and macrophage-dependent transendothelial migration

Abstract: Metastasis is a complex, multistep process of cancer progression that has few treatment options. A critical event is the invasion of cancer cells into blood vessels (intravasation), through which cancer cells disseminate to distant organs. Breast cancer cells with increased abundance of Mena [an epidermal growth factor (EGF)–responsive cell migration protein] are present with macrophages at sites of intravasation, called TMEM sites (for tumor microenvironment of metastasis), in patient tumor samples. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
132
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(137 citation statements)
references
References 50 publications
5
132
0
Order By: Relevance
“…These AUC values, where 0.8 is good, 0.7 is fair and 0.6 is poor discrimination (Metz, 1978), indicate that TMEM composite is better at predicting metastasis than these other prognostics (Harney et al, 2015;Oktay and Jones, 2015;Pignatelli et al, 2014;Robinson et al, 2009;Rohan et al, 2014;Roussos et al, 2011c;Wyckoff et al, 2007). Previous reports on cancer angiogenesis and vasculogenesis have collectively demonstrated that newly constructed endothelia are composed of myeloid precursors expressing the receptor tyrosine kinase Tie2 (also known as TEK) (Riabov et al, 2014;Squadrito and De Palma, 2011), and, more recently, the mannose-receptor c-type 1 (MRC1) (Hughes et al, 2015a).…”
Section: Molecular Profiling Of Metastatic Breast Cancer Cell Subpopumentioning
confidence: 93%
See 3 more Smart Citations
“…These AUC values, where 0.8 is good, 0.7 is fair and 0.6 is poor discrimination (Metz, 1978), indicate that TMEM composite is better at predicting metastasis than these other prognostics (Harney et al, 2015;Oktay and Jones, 2015;Pignatelli et al, 2014;Robinson et al, 2009;Rohan et al, 2014;Roussos et al, 2011c;Wyckoff et al, 2007). Previous reports on cancer angiogenesis and vasculogenesis have collectively demonstrated that newly constructed endothelia are composed of myeloid precursors expressing the receptor tyrosine kinase Tie2 (also known as TEK) (Riabov et al, 2014;Squadrito and De Palma, 2011), and, more recently, the mannose-receptor c-type 1 (MRC1) (Hughes et al, 2015a).…”
Section: Molecular Profiling Of Metastatic Breast Cancer Cell Subpopumentioning
confidence: 93%
“…Mena Calc is predictive of metastatic relapse and survival in breast cancer patients (Agarwal et al, 2012;Forse et al, 2015). The relative expression of Mena INV to Mena 11a is directly related to TMEM assembly because tumor cells that both assemble and use TMEM for dissemination require the expression pattern Mena INV-high and Mena11a low (Pignatelli et al, 2014) (see poster). TMEM sites are the sites of intravasation in polyoma middle T oncoprotein (PyMT)-induced mouse mammary tumors and patientderived xenograft (PDX) mammary tumors, and are therefore necessary for the dissemination step of the metastatic process (Harney et al, 2015).…”
Section: Molecular Profiling Of Metastatic Breast Cancer Cell Subpopumentioning
confidence: 99%
See 2 more Smart Citations
“…ns, nonsignificant. (48,49); however, analysis of tumors growing in WT or EN KO mice did not yield any significant differences in macrophage numbers, indicating that macrophages are not the driving force for endosialin-mediated tumor cell intravasation (C. K€ onig and H.G. Augustin, unpublished data).…”
Section: Discussionmentioning
confidence: 99%